Influence of Frying Methods on Quality Characteristics and Volatile Flavor Compounds of Giant Salamander (Andrias davidianus) Meatballs - Wengang Jin; Jinjin Pei; Xiaohua Chen; Jingzhang Geng; Dejing Chen; Ruichang Gao (Journal of Food Quality)
Effects of deep fat frying and hot air frying on texture, color difference, sensory score, yield, fat content, and volatile flavor compounds of giant salamander meatballs before and after frying were investigated. The results showed that, compared with the deep fat frying group, hot air-fried giant salamander meatballs had higher hardness, elasticity, and L∗ (p<0.05), but lower a∗, b∗ value, fat content, and yield (p<0.05). There was little distinction in sensory score, cohesiveness, and chewiness between the two frying methods (p>0.05). Gas chromatography ion migration chromatography (GC-IMS) was used for flavor compound analysis, and 50 flavor compounds were analyzed, containing 22 aldehydes, 11 ketones, 6 olefins, 4 acids, 3 esters, 3 alcohols, and 1 phenol. Compared with the samples before frying, the relative contents of aldehydes and ketones of fried giant salamander meatballs increased significantly, while the relative contents of esters and alkenes decreased significantly. Principal component analysis showed that the GC-IMS spectra of volatile flavor compounds before and after deep fat frying and hot air frying varied greatly, and the cumulative contribution rate of the two principal components reached 86.1%, indicating that the GC-IMS technology might be used to distinguish giant salamander meatballs before and after frying, or with different frying methods. These results may offer a note for development and quality control of the precooked giant salamander meatballs in the future.